Continuing professional development for interprofessional teams supporting patients in healthcare decision making - Lown, Beth A.; Kryworuchko, Jennifer; Bieber, Christiane; Lillie, Dustin M.; Kelly, Charles; Berger, Bettina; Loh, Andreas (Journal of interprofessional care, 2011)
Healthcare professionals and organizations, policy makers, and the public are calling for safe and effective care that is centered on patients’ needs, values, and preferences. The goals of interprofessional shared decision making and decision support are to help patients and professionals agree on choices that are effective, health promoting, realistic, and consonant with patients’ and professionals’ values and preferences. This requires collaboration among professionals and with patients and their family caregivers. Continuing professional development is urgently needed to help healthcare professionals acquire the knowledge, skills, and attitudes necessary to create and sustain a culture of collaboration. We describe a model that can be used to design, implement, and evaluate continuing education curricula in interprofessional shared decision making and decision support. This model aligns curricular goals, objectives, educational strategies, and evaluation instruments and strategies with desired learning and organizational outcomes. Educational leaders and researchers can institutionalize such curricula by linking them with quality improvement and patient safety initiatives.
Gesehen am 10.11.2022